Legal Liability of Securities Crowdfunding Platforms in Protecting Digital Investors: An Analysis of POJK No. 17 of 2025 - Lingga, Ebenni; Martono Anggusti; Ria Juliana Siregar (Universitas Islam Negeri Alauddin Makassar, 2026)
The Study aims to analyze the obligations of Securties Crowdfunding platform operators in omplementing due diligence and anti fraud strategiws, as well as ti determine the limits of their leal liability for investor losses under POJK Number 17 of 2025 and POJK Number 12 of 2025. This research employs a normative juridical method with statue and conceptual approach, supported by digital documentation studies and limited digital observation to examine the alignments between legal norms and their practical implementation. The finding that platform operatos play a strategyc role as gatekeepers in ensurig transoparency and investor protection through the implementation of due diligence and anti fraud mechanisms.However, in practice, these obligations have not been optimally in preventing post disbursement fraud, futhermore, a regulatory gap is identified regarding the absence of obligation to verify investor,s source of funds, This studry concludes that platform liability is conditional and must be determined base on the analysis of the causes of loss potentially extending ti civil, admnistrative. And criminal lability in the cases of negligence or legal violations.